Utilization of Online Learning Modules to Increase Nurse Capacity in the Implementation of Nursing Care Documentation - Irawan, Feri; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Nursing care documentation is still a problem in many developing countries due to individual and organizational factors. Providing education is believed to be able to improve the competence and compliance of nurses in documenting nursing care. This study analyzes the use of online learning modules to increase the capacity of nurses in the implementation of nursing care documentation at Rantau Prapat city administration public hospital. The type of research used is a quasi-experimental approach with a pre-post test design approach with a control group. The population in this study were all nurses in the inpatient ward of Rantau Prapatcity administration public hospital, totalling 160 people and a sample of 31 nurses for the intervention group and 31 nurses for the control group. Collecting data with primary and secondary data and the data were analyzed using the Mann–Whitney test. The results showed that there were differences in the knowledge, attitudes and actions of nurses regarding the documentation of nursing care before and after the online module learning was performed. The increase in scores on these three aspects was higher in the intervention group than in the control group. Clinical supervision by the head of the room is also recommended to be performed regularly and continuously so that nurses can be motivated in improving documentation that is oriented toward quality nursing care services. Abstrak: Pendokumentasian asuhan keperawatan masih menjadi permasalahan di berbagai negara berkembang dikarenakan faktor individual maupun faktor organisasional. Pemberian edukasi dipercaya mampu meningkatkan kompetensi dan kepatuhan perawat dalam melakukan pendokumentasian asuhan keperawatan. Penelitian ini bertujuan untuk menganalisis penggunaan modul pembelajaran online untuk meningkatkan kapasitas perawat dalam pelaksanaan pendokumentasian asuhan keperawatan di RSUD Rantau Prapat. Jenis penelitian yang digunakan adalah quasi experiment dengan pendekatan pre-post test design with control group. Populasi dalam penelitian ini adalah seluruh perawat pelaksana di ruang rawat inap RSUD Rantau Prapat yang berjumlah 160 orang dan sampel sebanyak 31 perawat untuk kelompok intervensi dan 31 perawat untuk kelompok kontrol. Pengumpulan data dengan data primer dan sekunder dan data dianalisis dengan uji Mann-Whitney. Hasil penelitian menunjukkan bahwa terdapat perbedaan pengetahuan, sikap dan tindakan perawat tentang pendokumentasian asuhan keperawatan sebelum dan sesudah dilakukan pembelajaran modul online. Peningkatan skor pada ketiga aspek tersebut lebih tinggi pada kelompok intervensi dibandingkan pada kelompok kontrol. Supervisi klinis oleh kepala ruangan juga dianjurkan untuk dilakukan secara teratur serta berkelanjutan agar perawat dapat termotivasi dalam meningkatkan pendokumentasian yang berorientasi pada pelayanan asuhan keperawatan yang berkualitas.